How Can We Better Prevent Obesity in Children? - Visscher, Tommy L. S. (Curr Obes Rep, 2015)
The aim of this review is to discuss the state of the art regarding the field of health promotion in the context of childhood obesity prevention in order to learn how we can better prevent childhood obesity. Challenges have been identified that exist within the different steps of health promotion programme development and implementation. Important steps forward include studying behaviours and determinants of behaviours as clusters, upgrading the importance of distal environmental factors in modelling determinants and understanding determinants as a dynamic system: a complex of interacting elements. An important note is that the process of implementation and the analysis thereof should more often come before the analysis of behaviours and the determinants of behaviour. In applied research, the expertise from the ‘real world’ practitioners should be used in an early stage to find out whether the answers on research questions really help us in preventing childhood obesity.